2020
DOI: 10.16948/zktipb.500935
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience in Peripartum and Postpartum Blood Transfusion Patients

Abstract: Amaç: Kliniğimizde doğum yapan hastaların prepartum, peripartum ve postpartum dönemdeki kan ve kan ürünleri transfüzyon endikasyonlarını literatür eşliğinde tartışmak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…This rate is similar to the study conducted by Seçen et al in our country. In the study by Seçen et al, it was seen that transfusions were pre-partum in 2.1%, intra-partum in 16.8%, and post-partum in 81% of patients (5). In the study by Madhushree et al, transfusion indications were found to be 58.4% anemia, 19.3% obstetric hemorrhage, and 3.8% thrombocytopenia (16).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This rate is similar to the study conducted by Seçen et al in our country. In the study by Seçen et al, it was seen that transfusions were pre-partum in 2.1%, intra-partum in 16.8%, and post-partum in 81% of patients (5). In the study by Madhushree et al, transfusion indications were found to be 58.4% anemia, 19.3% obstetric hemorrhage, and 3.8% thrombocytopenia (16).…”
Section: Discussionmentioning
confidence: 97%
“…Obstetric hemorrhages are the leading cause of maternal mortality and morbidity. These hemorrhages are responsible for 17.9% of maternal deaths in our country (5). The most common postpartum hemorrhages in obstetric cases are bleeding due to uterine atony.…”
Section: Introductionmentioning
confidence: 99%